2021
DOI: 10.1186/s12873-021-00539-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities in COVID-19 patients visiting the emergency department: a multicenter retrospective study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be associated with myocardial injury. Identification of at-risk patients and mechanisms underlying cardiac involvement in COVID-19 remains unclear. During hospitalization for COVID-19, high troponin level has been found to be an independent variable associated with in-hospital mortality and a greater risk of complications. Electrocardiographic (ECG) abnormalities could be a useful tool to identify patients at risk of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
9
0
4
Order By: Relevance
“…This may be due to the fact that in our institution, we prescribed HCQ/AZT combination regimen during a limited period (04/06/2020 to 04/16/2020) in a limited number of patients (n = 13) and ECG was not systematically performed. Other ECG abnormalities that we describe in our study are consistent with the literature ( 26 28 , 33 ). Interestingly, we found that left bundle branch block, S1Q3 pattern and repolarization abnormalities were independently associated with death in cases of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the fact that in our institution, we prescribed HCQ/AZT combination regimen during a limited period (04/06/2020 to 04/16/2020) in a limited number of patients (n = 13) and ECG was not systematically performed. Other ECG abnormalities that we describe in our study are consistent with the literature ( 26 28 , 33 ). Interestingly, we found that left bundle branch block, S1Q3 pattern and repolarization abnormalities were independently associated with death in cases of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…A fair number of studies have deepened the prognostic role of ECG in COVID-19 patients, finding significant combinations of various parameters with increased mortality or critical illness: signs of previous myocardial infarction [ 16 ], acute change in the ST tract and T wave [ 16 , 17 ], left bundle branch block [ 18 ], intraventricular block [ 19 ], premature atrial beats [ 19 ], right bundle branch block [ 19 ], right ventricular strain [ 20 ], fragmented QRS [ 21 ], heart rate variability [ 22 ], poor R wave progression [ 23 ], and lengthening of QTc interval and subsequent development of life-threatening arrhythmias [ 3 ]. COVID-19 increases the risk of myocarditis, but it appears that direct myocardial involvement in SARS-CoV-2 infection is relatively rare [ 24 ] compared to extensive evidence of ECG alterations or increased heart damage enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses have identified several ECG features that are related to a worse prognosis in COVID-19 (Fig. 4) [260][261][262][268][269][270][271][272][273]. Lowvoltage QRS complexes, previously shown to confer prognostic value in non-COVID-19 myocarditis [271], are also associated with increased mortality risk in COVID-19 patients [272].…”
Section: Prognostic Value Of Ecg Abnormalitiesmentioning
confidence: 99%